2014
DOI: 10.1021/am500903d
|View full text |Cite
|
Sign up to set email alerts
|

Hexaphenylbenzene-Based Fluorescent Aggregates for Ratiometric Detection of Cyanide Ions at Nanomolar Level: Set–Reset Memorized Sequential Logic Device

Abstract: A hexaphenylbenzene-based receptor 3 has been synthesized that forms a fluorescent spherical aggregate in mixed aqueous media due to its aggregation-induced emission enhancement attributes. These fluorescent spherical aggregates show ratiometric response toward cyanide ions via nucleophilic addition and undergo deaggregation to form smaller nanoaggregates. In addition, the solution-coated paper strips of 3 can detect cyanide ions in the range of ∼2.6 ng/cm(2), thus, providing a simple, portable, and low-cost m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 65 publications
(90 reference statements)
0
77
0
1
Order By: Relevance
“…Recently, Kumar et al [27] showed the importance of sequential logic circuits in creating memory devices to store information and perform operation through feedback loops, wherein one of the outputs of the device function as an input and is memorized as 'memory element'. Since, the present probe has shown "On-Off" switching behavior with Cu 2+ and F -ions we tried to implement the output emissions of respective chemical inputs, In1 (Cu 2+ ) and In2 (F -) in the construction of integrated and sequential logic circuit.…”
Section: On-off Switching Behavior Of 6 and Logic Implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Kumar et al [27] showed the importance of sequential logic circuits in creating memory devices to store information and perform operation through feedback loops, wherein one of the outputs of the device function as an input and is memorized as 'memory element'. Since, the present probe has shown "On-Off" switching behavior with Cu 2+ and F -ions we tried to implement the output emissions of respective chemical inputs, In1 (Cu 2+ ) and In2 (F -) in the construction of integrated and sequential logic circuit.…”
Section: On-off Switching Behavior Of 6 and Logic Implicationmentioning
confidence: 99%
“…According to truth table ( Figure 9B) sequential logic operations 6, 6+F -and 6+Cu 2+ +F -resulted high output emission (at 538 au) whereas, low output emission was obtained when logic operations 6+Cu 2+ and 6+F -+Cu 2+ were performed, respectively. Thus, the equipped sequential logic circuit signifies the set/reset element, and corresponds to the memory device ( Figure 9D) in which the two inputs: set (In2) and reset loop demonstrate a memory feature analogous to "write-read-erase-read" functions ( Figure 9C) [27] in which the reset input (In1 = 1) leads to a fluorescence turn-Off state (at 538 au) and encoded information in the system as "read" and "erased" and the logic operation is saved as "Output = 0". Further, the stored information within the system sends signal "write" by the set input (In2 = 1) and the fluorescence device reaches to turn-On state (at 538 au) and…”
Section: On-off Switching Behavior Of 6 and Logic Implicationmentioning
confidence: 99%
“…12 The general experimental methods, quantum yield calculations, and materials used are same as reported earlier by us. 12 The TEM images were recorded using a HR-TEM-JEM 2100 microscope. The FT-IR spectra were recorded using a VARIAN 660 IR spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…These compounds are weakly-emissive or non-emissive in solution, but exhibit intense emission upon aggregate formation, that is opposite to what we are known as aggregation-caused quenching (ACQ). Furthermore, their unique AIEE effect has also been successfully applied to develop fluorescent sensors [8][9][10][11], logic system modulation [12,13], electroluminescent materials [14][15][16] and so on.…”
Section: Introductionmentioning
confidence: 99%